The IntelliCage System: A Review of Its Utility as a Novel Behavioral Platform for a Rodent Model of Substance Use Disorder - Iman, Ismail Nurul; Yusof, Nurul Aiman Mohd; Talib, Ummi Nasrah; Ahmad, Nur Aimi Zawami; Norazit, Anwar; Kumar, Jaya; Mehat, Muhammad Zulfadli; Jayabalan, Nanthini; Muthuraju, Sangu; Stefaniuk, Marzena; Kaczmarek, Leszek; Muzaimi, Mustapha (Frontiers in Behavioral Neuroscience, 2021)
The use of animal models for substance use disorder (SUD) has made an important contribution in the investigation of behavioral and molecular mechanisms underlying substance abuse and addiction. Here we review a novel and comprehensive behavioral platform to characterize addiction-like traits in rodent using a fully automated learning system, the IntelliCage. This system simultaneously captures basic behavioral navigation, reward preference and aversion, as well as multi-dimensional complex behaviors and cognitive functions of group-housed rodent. It can reliably capture, and track locomotor and cognitive pattern alterations associated with the development of substance addiction. Thus, the IntelliCage learning system offers a potentially efficient, flexible, and sensitive tool for high-throughput screening of rodent SUD model.